Kecenderungan Minat Murid Pintar Dan Berbakat Muslim Dalam Bidang Sains - Muhammad Abrar Zamri; Norazlina Subani; Rosita Zainal; Mohamad Azani Abd Kadir Jailani; Liyana Amalina Adnan; Ahmad Hakimi Shaffie; Faizatul Atirah Fadzil Zabidee; Ehwan Ngadi; Adnan Mohamed Yusoff (2024)
E-Proceedings 3rd Insan Junior Researchers International Conference 2022 (iJURECON 2022) : "STREAM for a better future”/Editors: Rahayu Ahmad, Muhammad Azan Tamar Jaya, Ahmad Fuad Mohamad Amin, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan. 21-23rd October 2022 (Virtual Conference) Organized By : Kolej Genius Insan,USIM